Pengelolaan Obat pada Tahap Seleksi dan Pengadaan di Instalasi Farmasi RSUD Kota Surakarta - Soka, Burhanudin Gasim; Merari P., Jason; Oetari, Oetari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Hospital management is an important part of drug management, especially the selection and procurement stages of drug management in hospitals. This study aims to analyze drug management at the drug selection and procurement stage at Surakarta City Hospital in 2017. The study used a descriptive design for retrospective and concurrent data. Data were collected qualitatively and quantitatively through interviews. The data obtained from the drug selection and procurement stages were analyzed based on indicators, then compared with standards and results of other studies. The results of the research at the drug selection stage, the percentage of conformity of drug items with FRS was 94.7%, the percentage of conformity of drug items with FORNAS was 86.83%. At the drug procurement stage, the percentage of available capital funds with the required funds is 136.05%, the percentage of drug procurement fund allocation is 32.56%, the frequency of procurement of each drug item per year, the average drug procurement is 12 times in the medium category, the frequency of conformity order letters with invoices 0 times, the frequency of delays in payment by the hospital against the agreed time 0 times, the percentage of the number of drug items that were procured as planned was 84.77%.Keywords: drug management; drug selection; drug procurement; pharmaceutical installation ABSTRAK Manajemen rumah sakit merupakan bagian penting dari pengelolaan obat, terutama tahap seleksi dan pengadaan dari pengelolaan obat di rumah sakit. Penelitian ini bertujuan untuk menganalisis pengelolaan obat pada tahap seleksi dan pengadaan obat di RSUD Kota Surakarta tahun 2017. Penelitian menggunakan rancangan deskriptif untuk data yang bersifat retrospektif dan concurrent. Data dikumpulkan secara kualitatif dan kuantitatif melalui wawancara. Data yang diperoleh dari tahap seleksi dan pengadaan obat dianalisis berdasarkan indikator, kemudian dibandingkan dengan standar dan hasil penelitian lain. Hasil penelitian pada tahap seleksi obat, persentase kesesuaian item obat dengan FRS 94,7%, persentase kesesuaian item obat dengan FORNAS 86,83%. Pada tahap pengadaan obat, persentase modal dana yang tersedia dengan dana yang dibutuhkan 136,05%, persentase alokasi dana pengadaan obat 32,56%, frekuensi pengadaan tiap item obat per tahun, rata-rata pengadaan obat 12 kali dalam kategori sedang, frekuensi kesesuaian surat pesanan dengan faktur 0 kali, frekuensi tertundanya pembayaran oleh rumah sakit terhadap waktu yang disepakati 0 kali, persentase jumlah item obat yang diadakan dengan yang direncanakan 84,77%.Kata kunci: pengelolaan obat; seleksi obat; pengadaan obat; instalasi farmasi